Upaya BP Batam Dalam Mengembangkan Pembangunan Di Kota Batam - Nathasia Angelina Saragi; Omi Omi; Mellyana Candra (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Batam is the authority responsible for developing the growth of the Batam island industrial area, authority over the allocation and use of land in order to carry out the development of Batam as an industrial area. The Batam Authority, which is currently called the Batam Free Trade Zone and Free Port Concession Agency (abbreviated as BP Batam) is a central government institution/agency formed based on the Government Regulations of the Republic of Indonesia. This research uses literature review and interviews to get an idea of the efforts of the Batam city government. in the development developments in the city of Batam, therefore in this article there are various sources of data and references. The data collection method is a method used to find various sources of data needed for research. Future plans for the development of BP Batam will continue and it is planned that until 2029 development in the city of Batam will continue to be encouraged in order to support economic products so that they are even better, even the development carried out by BP Batam is an extension of the development of Rempang, because in Rempang several companies such as glass companies and also companies operating in the tourism sector will be built in Rempang. BP Batam also shows its seriousness in developing Batam City by implementing a number of strategic infrastructure projects such as highways and airport development. BP Batam also plans to develop Rempang Island to become a new driving force for Indonesia's economic growth.